Pengaruh Efisiensi Operasional, Leverage, dan Ukuran Perusahaan terhadap Kinerja Keuangan pada Perusahaan Manufaktur Subsektor Makanan dan Minuman yang Terdaftar di Bei Periode 2022-2024 - Dwi Wulandari; Faisol Faisol; Diah Nurdiwaty (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
The food and beverage subsector of the manufacturing industry, despite experiencing positive growth, still faces challenges in maintaining financial performance stability, such as high operational costs, suboptimal capital structure, and efficiency differences across company scales. This study aims to examine the effect of operational efficiency, leverage, and firm size on financial performance, both partially and simultaneously, in food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2022–2024 period. The sample consists of 16 companies selected using purposive sampling, with a total of 48 observations. This research applies a quantitative approach using panel data regression analysis and hypothesis testing through partial (t-test) and simultaneous (F-test) methods with STATA version 14. The best model used is the Random Effect Model (REM), selected through Chow, Hausman, and Lagrange Multiplier tests. The findings indicate that leverage has a significant negative effect on financial performance when tested partially, while operational efficiency and firm size do not have a significant partial effect. However, when tested simultaneously, operational efficiency, leverage, and firm size significantly influence the financial performance of food and beverage manufacturing companies listed on the IDX.